Economic approach to nature conservation - Land use change - Pedro Nogueira (European Regional Science Association (ERSA), 2015)
The relationship between land use and biodiversity is important to understand the decision support systems in order to attain sustainability. Nowadays, land use and biodiversity management is focused on protected areas, discarding other habitats, tending to favor exclusive property rights over the territory, thus creating unfeasible solutions for society. Azores has 420 endemic species and subspecies, being these protected by the Directives of Habitats and Birds. A better understanding of endemic species value is a remarkable tool to preserve biodiversity, thus affecting social welfare. The aim of this paper is to understand the relationship between land use and endemic species richness. For this, spatial endemic richness for different taxa (Bryophytes, Vascular Plants, Mollusks, Arthropods and Vertebrate) was identified at the spatial scale. After that was use SPSS and Geoda to explain endemic species richness with the mosaic of land uses and underlying environmental conditions, to allow soil use management and conservation measures to be determined through the integrated organization of landscape and not only by the definition of protected areas. First, we selected particular places where land use decisions were taken, reflecting trade-offs and through the opportunity cost of different land uses and the implicit values of different degrees of endemic species. After that, we determined estimated models considering neighborhood effects between geographical units, using GeoDa. Results are consistent and explain in a much adjusted way the relationship between land use and endemic species richness, allowing to determine the existent trade-offs between land use and species richness.
Keywords: 330; Biodiversity conservation; land use; spatial interaction; integrated management; opportunity cost